Study of the Osteoinductor Property in Bone Repair of the Species Zingiber Zerumbet (Bitter Ginger) (Research, Society and Development, 2023)
Zingiber zerumbet is a species that is part of the Zingiberaceae family, one of the largest families in the plant kingdom, being considered a perennial, aromatic and tuberculin plant. This species has been used in different sectors as food due to its nutritional properties. The main chemical compounds found in Z. zerumbet are terpenes and polyphenols. Zerumbone, a sesquiterpene, is the main bioactive compound of Z. zerumbet and is widely studied for its medicinal properties. Although many studies have already reported on its pharmacological properties, extract and metabolites granted from the species of Z. zerumbet exhibited anti-inflammatory, antioxidant, antidiabetic, anticancer, antimicrobial, analgesic and antiviral properties. Several biomaterials have been developed to fill or rebuild bone defects, among these, the herbal ones that have substances with high antioxidant potential stand out, not which this one has a role in the bone recovery process. Therefore, this mini-review provides an overview of the main aspects related to the properties of bioactive compounds found not extracted from Z. zerumbet species, with the objective of demonstrating the importance of extracted actives and used in future osteoinductive solutions.